UUCG RNA Tetraloop as a Formidable Force-Field Challenge for MD Simulations - Mráziková, Klaudia; Mlýnský, Vojtěch; Kührová, Petra; Pokorná, Pavlína; Kruse, Holger; Krepl, Miroslav; Otyepka, Michal; Banáš, Pavel; Šponer, Jiří (Journal of chemical theory and computation, 2020)
Explicit solvent atomistic molecular dynamics (MD) simulations represent an established technique to study structural dynamics of RNA molecules and an important complement for diverse experimental methods. However, performance of molecular mechanical (MM) force fields (ff's) remains far from satisfactory even after decades of development, as apparent from a problematic structural description of some important RNA motifs. Actually, some of the smallest RNA molecules belong to the most challenging systems for MD simulations and, among them, the UUCG tetraloop is saliently difficult. We report a detailed analysis of UUCG MD simulations, depicting the sequence of events leading to the loss of the UUCG native state during MD simulations. The total amount of MD simulation data analyzed in this work is close to 1.3 ms. We identify molecular interactions, backbone conformations, and substates that are involved in the process. Then, we unravel specific ff deficiencies using diverse quantum mechanical/molecular mechanical (QM/MM) and QM calculations. Comparison between the MM and QM methods shows discrepancies in the description of the 5'-flanking phosphate moiety and both signature sugar-base interactions. Our work indicates that poor behavior of the UUCG tetraloop in simulations is a complex issue that cannot be attributed to one dominant and straightforwardly correctable factor. Instead, there is a concerted effect of multiple ff inaccuracies that are coupled and amplifying each other. We attempted to improve the simulation behavior by some carefully tailored interventions, but the results were still far from satisfactory, underlying the difficulties in development of accurate nucleic acid ff's.
Keywords: simulace molekulární dynamiky; Base Sequence; sekvence nukleotidů; RNA; konformace nukleové kyseliny; Nucleic Acid Conformation; Density Functional Theory; Molecular Dynamics Simulation; teorie funkcionálu hustoty